Negative Stigma Against Salafi Women in the Hidayatul Muslimin I Islamic Boarding School Environment - Rizky Septia Utami Bafadal; Ghea Rae Sabrina; Dita Pratiwi (CV. Edujavare Publishing, 2026)
This study aims to analyze the negative stigma toward Salafi women among students at Hidayatul Muslimin I Islamic Boarding School, Kubu Raya Regency, and to identify the forms of stigma, their impacts on social interaction and psychosocial well-being, as well as the adaptation strategies employed by the students. The study adopted a mixed-methods approach by administering questionnaires to students and conducting descriptive analysis of the collected data. The analysis was based on the dimensions of public stigma, self-stigma, discrimination, social interaction, psychosocial impact, social support, and adaptation strategies using Erving Goffman's Social Stigma Theory as the analytical framework. The findings indicate that Salafi women continue to experience stigma in the form of stereotypes and prejudice associated with their religious appearance. Nevertheless, most respondents maintained positive social interactions and received support from their families, peers, and educational environment. The psychosocial effects were generally reflected in feelings of discomfort resulting from negative public perceptions, while the primary adaptation strategies included ignoring negative comments, strengthening self-confidence, providing explanations to others, and maintaining their religious identity. The study highlights the importance of promoting inclusive education and diversity literacy to reduce stigma toward religious minority groups within educational settings.Keywords: three to five keywords in alphabetical order